Design and optimization of an automatic hydraulic steer-by-wire system for an agricultural chassis - Jin, Yinhao; Yuan, Yanwei; Zhu, Licheng; Wang, Decheng; Zhao, Bo; Fang, Xianfa (International Journal of Agricultural and Biological Engineering, 2022)
To meet the requirements of fast steering at low vehicle speed and slow steering at high vehicle speed, the automatic steering of agricultural chassis must control both the wheel steering angle and the steering angle’s angular speed. This study applied hydraulic steer-by-wire technology to the automatic steering control of agricultural chassis. First, the transmission mechanism of the designed steering system was optimized. According to the rule of least squares, aiming at the minimum sum of squares of errors between 10 ideal outer wheel angles and real outer wheel angles, the optimal solution of hole spacing on both sides of the steering hydraulic cylinder piston rod was 925 mm. The outer wheel angle error of the optimized steering mechanism throughout the steering stroke was less than 0.15°. Additionally, a hydraulic steer-by-wire system was developed, and the parameters of its critical components were calculated. Then, the compound control strategy of the steering cylinder piston rod displacement and moving speed was formulated for this automatic steering system. The entire control system included a valve control signal calculation model, an initial velocity calculation model, a correction velocity calculation model, and an attenuation velocity calculation model, and the formulae of each model were deduced. Based on the optimized parameters and the developed control strategy, a simulation model was built in AMESim, and simulation results showed that the proposed control strategy could achieve simultaneous controls of piston rod displacement and speed at different vehicle speeds and loads. The horizontal and vertical displacements of the right wheel center were plotted for typical vehicle speeds and steering commands. The results of this study provided a new idea for the application of hydraulic steer-by-wire technology in the automatic steering of agricultural chassis. Keywords: optimal design, steering mechanism, automatic steering, simulation analysis DOI: 10.25165/j.ijabe.20221501.6755 Citation: Jin Y H, Yuan Y W, Zhu L C, Wang D C, Zhao B, Fang X F. Design and optimization of an automatic hydraulic steer-by-wire system for an agricultural chassis. Int J Agric & Biol Eng, 2022; 15(1): 132–138.